Children's language use in ECEC in a child perspective. Issue 4 (2nd October 2021) - Ahrenkiel, Annegrethe; Holm, Lars; Eilenberg, Laura Østergaard
ABSTRACT: With inspiration from research in linguistic ethnography and children's perspectives, this article examines children's language use in Early Childhood Education and Care (ECEC) in a child perspective. The article is based on ethnographic fieldwork including video recordings from four children's entire days in a Danish day care centre. A multimodal analysis of an extended play sequence demonstrates how children's interactional language use is a creative and collective process that provides multiple opportunities to use and develop language practices, where children constantly align with each other to continue their common endeavours. The findings point to a need for broadening the conceptual understanding of language and of children's language learning as an integral part of children's everyday life in ECEC.